Tindak Tutur dalam Tayangan Kanal Youtube WAW Entertaiment - Pratiwi, Dyah (Universitas Suryakancana, 2023)
The development of the times makes the media for communication become increasingly widespread. This also affects speech acts both orally and in writing. Oral speech can be found on social media. This article will describe the speech acts of locutionary, illocutionary, and perlocutionary in the WAW Entertainment YouTube channel, episode